2010
DOI: 10.1248/jhs.56.20
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effects of Oral Administrated Ascorbic Acid against Oxidative Stress and Neuronal Damage after Cerebral Ischemia/Reperfusion in Diabetic Rats

Abstract: Diabetes enhances oxidative stress and exacerbates acute ischemic injury. Previous studies have demonstrated that infarct volumes were greater in diabetic animals caused by a transient cerebral ischemia as compared with nondiabetic animals. Ascorbic acid (AA) as a naturally occurring major antioxidant is reported to be low in diabetic tissues. Therefore, we examined the effects of daily supplementation of AA on lipid peroxidation and the activity of antioxidant enzymes (superoxide dismutase, catalase and gluta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 45 publications
3
11
0
Order By: Relevance
“…Recycling of tocopheroxyl radicals to tocopherol is achieved with ascorbic acid (Lobo et al, 2010). In our study, ascorbic acid was decreased in diabetic rats as reported earlier (Iwata et al, 2010). Reduction in liver and kidney ascorbic acid levels may occur due to excessive oxidation and lack of regeneration from their radical form to reduced form.…”
Section: Effect Of Etbc On Non-enzymatic Antioxidants In Tissuesupporting
confidence: 82%
“…Recycling of tocopheroxyl radicals to tocopherol is achieved with ascorbic acid (Lobo et al, 2010). In our study, ascorbic acid was decreased in diabetic rats as reported earlier (Iwata et al, 2010). Reduction in liver and kidney ascorbic acid levels may occur due to excessive oxidation and lack of regeneration from their radical form to reduced form.…”
Section: Effect Of Etbc On Non-enzymatic Antioxidants In Tissuesupporting
confidence: 82%
“…The protective role of antioxidant such as α-tocopherol, ascorbic acid and methionine is reducing the lipid peroxidation as evidenced by a decreased MDA concentration in the brain because of Pb-induced oxidative stress. 27) Taking these findings together, it is suggested that oxidative stress, which is induced by lead, is recovered by natural antioxidants, such as ascorbic acid, 28) epigallocatechin-3-gallate 29) and plant extracts etc. 30,31) Marine algae have the potential to improve the biochemical imbalances induced by various toxins associated with free radicals.…”
Section: Introductionmentioning
confidence: 99%
“…Impairment of these antioxidant enzymes caused by nonenzymatic glycation is responsible for the increase of lipid peroxidation in the brain of diabetic animals. In a previous study, we also observed that the level of lipid peroxidation marker TBARS (thiobarbituric acid reactive substances) was elevated and activity of SOD, CAT and GPx was decreased in STZ-induced diabetic rat brain, which were reversed by chronic treatment of ascorbic acid (Iwata et al, 2010). Thus, the enhanced oxidative stress in diabetes is considered to cause functional impairment of antioxidant enzymes and the resulting diminution in antioxidative defense leads to further enhancement of radical reactions and other dysfunctions in the brain.…”
Section: Discussionmentioning
confidence: 76%
“…Focal cerebral ischemia was induced by MCAO with a standard intraluminal filament technique as previously described (Iwata et al, 2010). The animals were anesthetized with 4% halothane and maintained with 1.5% halothane and 30% oxygen under spontaneous respiration.…”
Section: Middle Cerebral Artery Occlusion and Reperfusionmentioning
confidence: 99%